2016
DOI: 10.1038/ncomms12296
|View full text |Cite
|
Sign up to set email alerts
|

Population decline is linked to migration route in the Common Cuckoo

Abstract: Migratory species are in rapid decline globally. Although most mortality in long-distance migrant birds is thought to occur during migration, evidence of conditions on migration affecting breeding population sizes has been completely lacking. We addressed this by tracking 42 male Common Cuckoos from the rapidly declining UK population during 56 autumn migrations in 2011–14. Uniquely, the birds use two distinct routes to reach the same wintering grounds, allowing assessment of survival during migration independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
169
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(183 citation statements)
references
References 28 publications
(38 reference statements)
7
169
1
1
Order By: Relevance
“…Future studies estimating survival values for Reed Warblers wintering in Africa would enable a more accurate estimation of mortality rates during migration. Intriguingly, our results and conclusions are in agreement with a recent study of satellite-tracked Common Cuckoos Cuculus canorus that showed precisely where bird mortality occurred (Hewson et al 2016). The authors found that most of the mortality of Common Cuckoos on the Western migratory route occurred in Europe, prior to completion of the Sahara crossing, leading them to suggest that deteriorating conditions at stopover sites in Spain and Morocco were responsible for the decreased survival.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Future studies estimating survival values for Reed Warblers wintering in Africa would enable a more accurate estimation of mortality rates during migration. Intriguingly, our results and conclusions are in agreement with a recent study of satellite-tracked Common Cuckoos Cuculus canorus that showed precisely where bird mortality occurred (Hewson et al 2016). The authors found that most of the mortality of Common Cuckoos on the Western migratory route occurred in Europe, prior to completion of the Sahara crossing, leading them to suggest that deteriorating conditions at stopover sites in Spain and Morocco were responsible for the decreased survival.…”
Section: Discussionsupporting
confidence: 81%
“…low food availability), it seems likely that a large proportion of the mortality which occurs in avian species is associated with this stage of the annual cycle. Several studies have provided evidence for this hypothesis (Newton 2006;Bayly et al 2011;Klaassen et al 2014, Hewson et al 2016. For example, Sillett and Holmes (2002) estimated that mortality rates of Blackthroated Blue Warblers Dendroica caerulescens were at least 15-fold higher during migration than during stationary periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Het aantal locaties met herhaalde waarnemingen in (Halupka et al 2008;Hewson et al 2016;Zwarts et al 2009). Een achteruitgang van insectenpopulaties kan bijdragen aan een neerwaartse populatietrend, maar het is onwaarschijnlijk dat deze zich hierin een-op-een vertaalt.…”
Section: Loopkevers En Snuitkeversunclassified